Natur på skolgård - Lidberg, Emma (2007)
As a result of my fascination for nature I have chosen to study the possibilities to introduce natural environments on schoolyards. Too many schoolyards are lacking vegetation and many of them look like sterile asphalt deserts. The master thesis consists of two parts. The first part is based on literature studies and the second part in which findings from part one are put into practice. Five examples are presented; four schoolyards in Malmö; Kryddgårdsskolan, Kirsebergsskolan, Rörsjöskolan and Lindängeskolan and one in Kalmar; Åbyskolan. Malmö Naturskola has been working with the chosen areas on the schoolyards in Malmö. Malmö Naturskola is working with introducing children to nature by different means. The ideas here presented, using nature areas or "hills" is to create an exiting playground that could give nature experiences in breaks and during outdoor lectures. The possibility to organize outdoor lectures can contribute to an increased learning, when the teachers can act as a collaborator or a leader during the outdoor lectures which mean that a common learning is favoured. Natures on schoolyards are assets that can be used for learning and inspiration sources in most subjects in school. To get an understanding for why the schoolyards looks like they do, I made a historical research and describes the school gardens development from the 1840th to the decline about when the functionalism was introduced in the 1940s. During the 90´s the schoolyards was not of public matter anymore but after that it seemed to be growing interest for green ideas and values again. In my literature study, I also focused on the pedagogic values of natural environment for children and how natural environment can be enchained by good design. I found out that children that got access to a natural environment develop their mind better both physically and socially than these who haven't that access. Children with access to natural environment plays more games, plays better together with others and are more persistent in their games. The design of a schoolyard is important. Changes of the place are important. The temporal and seasonal changes make the children understand time easier. The natural environment gives many surprises and is always changing. It is important that places are accessible for the children in that way that they, the children make them their own. To be able to make places to feel as their own, children have to be able to put their traces and make mess in the nature without that anyone is cleaning up. The natural environment gives the children a personal feeling for the nature. That feeling and to feel participation gives a stronger sense of responsibility leading to a more beautiful environments and less damage.